2015
DOI: 10.1002/uog.14639
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance during embryo transfer: a systematic review and meta‐analysis of randomized controlled trials

Abstract: The available evidence suggests that there is a benefit of using US guidance during ET. However, both US-guided transfer and clinical touch should be considered acceptable, as the benefit of US is not large and should be balanced against the increased cost and need to change the catheter type. More studies are required before conclusions can be drawn regarding the effect of other techniques on reproductive outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 53 publications
0
31
0
1
Order By: Relevance
“…Where a significant difference was observed, we determined the number needed to treat for an additional beneficial outcome (NNTB) or an additional harmful outcome (NNTH). A random‐effects model was chosen because we should not assume that the true‐effect size is the same across studies as doses were different; additionally a random‐effects model incorporates the observed heterogeneity among studies, obtaining more conservative CIs.…”
Section: Methodsmentioning
confidence: 99%
“…Where a significant difference was observed, we determined the number needed to treat for an additional beneficial outcome (NNTB) or an additional harmful outcome (NNTH). A random‐effects model was chosen because we should not assume that the true‐effect size is the same across studies as doses were different; additionally a random‐effects model incorporates the observed heterogeneity among studies, obtaining more conservative CIs.…”
Section: Methodsmentioning
confidence: 99%
“…Endometrial thickness (EnT) directly reflects histological thickness, while endometrial pattern (EnP) changes in lockstep with the menstrual cycle, correlating closely with morphologic assessment of endometrial biopsies (24,25). While endometrial histology has long been recognized to inform the optimal window of implantation (26), the influence of EnT and EnP on endometrial receptivity and pregnancy rates (PR) has been intensively explored but not conclusively answered (27,28). …”
Section: Introductionmentioning
confidence: 99%
“…In all women (Group A and Group B), transfers were performed by the same operator, without difficulty, under ultrasound guidance, up to 1.5 cm from the uterine fundus, using a 18-cm Wallace Sure View Embryo Replacement catheter (CE118) [20].…”
Section: Methodsmentioning
confidence: 99%